Pandemic borders policy: securitizing stateless people during COVID-19 in Sabah, Malaysia - Yunos, Siti Salwa Mohd; Fernandez, Kevin; Subramaniam, Gayathri Muruga (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
Drawing on Copenhagen School securitization theory, this study investigates how the COVID-19 pandemic accelerated the securitization of stateless migration in Sabah, Malaysia. Stateless communities, already excluded from healthcare, employment, and social protection, became increasingly framed as existential threats to public health during a period marked by both pandemic crisis and federal political instability. The analysis focuses on the timeframe from March 18, 2020 to August 16, 2021, when the sudden change of federal government intensified securitization rhetoric, as the new administration sought to consolidate legitimacy through migration control. This research identifies two interlinked securitization strategies. First, punitive measures such as mass arrests, prolonged detention, and deportations symbolized state authority while addressing public anxieties. Second, deterrence mechanisms including reinforced border patrols, visible security deployments, and integrated security operations expanded surveillance and control over marginalized populations. While these measures temporarily reduced unauthorized border crossings, they also deepened the marginalization of stateless communities, producing family separations and heightened social tensions. By situating stateless migration at the intersection of public health and national security, this study underscores the urgency of examining how political crises shape securitization processes and contributes to broader debates on human security, migration governance, and state legitimacy under pandemic conditions.